Analisis Career FOMO, Kepuasan Kerja dan Stres Kerja Terhadap Keinginan Pindah Kerja Karyawan Generasi Z Di BFI Finance: Analysis of Career FOMO, Job Satisfaction and Work Stress on the Desire to Change Jobs of Generation Z Employees at BFI Finance - Irma Wahyuningsih; Puput Tri Handayani; Ahmad Sahdeli; Alip Nur Sigit; Deni Adi Setiawan; Ismi Fauziah Ruslani; Muhammad Ridho; Rifkhan Rifkhan (CV Warnak Johanna Nusantara, 2026)
Abstracts - This study aims to analyze the effect of Career FOMO, job satisfaction, and job stress on turnover intention among Generation Z employees at BFI Finance. Generation Z exhibits unique characteristics in perceiving careers, one of which is the increasing phenomenon of Career FOMO, defined as the fear of being left behind in professional development. This study is grounded in the Theory of Planned Behavior (TPB), which explains that behavioral intention is influenced by attitudes toward behavior, subjective norms, and perceived behavioral control. In this context, Career FOMO, job satisfaction, and job stress are positioned as factors shaping turnover intention. This study employs a quantitative approach using a survey method involving 100 Generation Z employees at the headquarters of BFI Finance in Serpong, BSD. Data were analyzed using multiple linear regression. The results indicate that Career FOMO, job satisfaction, and job stress simultaneously have a significant effect on turnover intention, with a contribution of 55.1%. Partially, Career FOMO and job stress have a positive effect on turnover intention, while job satisfaction has a negative effect. Career FOMO is identified as the most dominant factor influencing turnover intention among Generation Z employees. These findings provide practical implications for management in designing more effective employee retention strategies aligned with the psychological and career-related characteristics of Generation Z.